-2x+1+7x=6

Simple and best practice solution for -2x+1+7x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+1+7x=6 equation:


Simplifying
-2x + 1 + 7x = 6

Reorder the terms:
1 + -2x + 7x = 6

Combine like terms: -2x + 7x = 5x
1 + 5x = 6

Solving
1 + 5x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 5x = 6 + -1

Combine like terms: 1 + -1 = 0
0 + 5x = 6 + -1
5x = 6 + -1

Combine like terms: 6 + -1 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| -3(t-1)+5t=4t-7 | | 10(-6)-6=11(-6) | | 13+2(4c-2)=29 | | 2x+4-8=0 | | 2a(b+2c)= | | x+3x+14=102 | | 7+3x=5+13 | | 21x-1=19x+11 | | -15x-20=-13x+120 | | X-5/7=x+3/2 | | 7(4x+1)=3x-7x | | X+5+x=19 | | -8-7=6x+9-5x | | 8x+4=7x+11 | | 3x-4-4x=6 | | 4W=-29 | | -3+quaterz=1 | | -6(v+4)+4v+6=7v+6 | | 2(5x+1)=4x-8x | | 3xx+15x-6=180 | | 4x+4+6x=64 | | 6x-3=6(x+3) | | -0.5x+7.68=-0.7x+6.48 | | 2p+9q=36 | | 16(2x-7)=4(8x+5) | | 6x+2x-5=35 | | A=a+b+c/3 | | 2(5x+6)=-33+35 | | x/10=5/12 | | x/9=36 | | 5/8x+1/16x=11/16x | | 18+10x+x^2=0 |

Equations solver categories